2009
DOI: 10.1016/j.micpath.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion and biocide resistance in nontypeable Haemophilus influenzae biofilms

Abstract: Respiratory infections caused by nontypeable Haemophilus influenzae (NTHi) are a major medical problem. Evidence suggests that the ability to form biofilms on mucosal surfaces may play a role in NTHi pathogenesis. However, the factors that contribute to NTHi biofilm cohesion remain largely unknown. In this study we investigated the biofilm growth and detachment phenotypes of eight NTHi clinical strains in vitro. We found that the majority of strains produced biofilms within 6 hours when cultured statically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Biofilms are well known to display a high degree of resistance to antibiotic and biocide treatments (17,21,32). In agreement with previous studies (5, 10, 13, 26), we confirm here that P. aeruginosa biofilm cells displayed resistance to PAA (an oxidizing agent) and more markedly BAC (a quaternary ammonium compounds) that was greater than that of their planktonic counterparts.…”
Section: Discussionsupporting
confidence: 93%
“…Biofilms are well known to display a high degree of resistance to antibiotic and biocide treatments (17,21,32). In agreement with previous studies (5, 10, 13, 26), we confirm here that P. aeruginosa biofilm cells displayed resistance to PAA (an oxidizing agent) and more markedly BAC (a quaternary ammonium compounds) that was greater than that of their planktonic counterparts.…”
Section: Discussionsupporting
confidence: 93%
“…Biofilm formation by all tested NT H. influenzae isolates was sensitive to proteinase K, suggesting that proteins play an important role in adhesion and biofilm formation. Izano et al demonstrated rapid biofilm detachment in eight NT H. influenzae isolates after adding proteinase K and suggested that adhesins existed within the biofilm structure (44). Our study significantly expands this observation based on a large collection of NT H. influenzae isolates from different sources.…”
Section: Fig 3 Distribution Within the Nt H Influenzae Clinical Soursupporting
confidence: 75%
“…The key role of e DNA for initial bioWlm formation was shown for S. pneumoniae, E. faecalis, S. aureus, S. epidermidis, H. inXuenzae, and-by our own investigations-N. meningitidis [64][65][66][67][68][69]. Theoretically, DNA in bioWlms can be released by diVerent mechanisms such as autolysis, by DNA containing outer-membrane vesicles or by DNA secretion systems.…”
Section: Bacterial Biowlmsmentioning
confidence: 56%